2003
DOI: 10.1021/bp025665e
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Low-Temperature Plasmas on Deinococcus radiodurans and Biomolecules

Abstract: The effects of cold plasma on Deinococcus radiodurans, plasmid DNA, and model proteins were assessed using microbiological, spectrometric, and biochemical techniques. In low power O(2) plasma (approximately 25 W, approximately 45 mTorr, 90 min), D. radiodurans, a radiation-resistant bacterium, showed a 99.999% reduction in bioburden. In higher power O(2) plasma (100 W and 500 mTorr), the reduction rate increased about 10-fold and observation by atomic force microscopy showed significant damage to the cell. Dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
61
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 38 publications
(35 reference statements)
11
61
1
Order By: Relevance
“…[4][5][6] In contrast, our results show only a weak (below 10%) multifragmentation of DNA, which is observed as smeared bands in the gel image.…”
mentioning
confidence: 55%
“…[4][5][6] In contrast, our results show only a weak (below 10%) multifragmentation of DNA, which is observed as smeared bands in the gel image.…”
mentioning
confidence: 55%
“…Low-pressure oxygen plasma has been shown to degrade lipids, proteins and DNA of cells (Mogul et al 2003). The reactive species in plasma have been widely associated to the direct oxidative effects on the outer surface of microbial cells.…”
Section: Action On Cell Components and Functionsmentioning
confidence: 99%
“…Many groups already demonstrated that plasma treatment can lead, under appropriate operational conditions, to fast sterilisation of different strains of bacteria or bacterial spores, [10][11][12][13][14] depyrogenation of bacterial endotoxins, [14][15][16][17][18] or to efficient elimination of protein residuals from surfaces. [14,[19][20][21][22][23][24][25] Plasma treatment of surfaces as a sterilisation or decontamination method is a promising approach to overcome limitations of conventional techniques. The precise characterisation of the employed plasma discharges, the application of sensitive surface diagnostic methods and targeted experiments to separate the effects of different agents, have led to rapid progress in the understanding of different relevant elementary processes.…”
Section: Introductionmentioning
confidence: 99%